Phenotypic and Genetic Diversity Analysis of 18 Ornamental Strawberries - Chaocui Nong; Jiayi Hou; Jin He; Yanju Zheng; Shugen Yang; Lai Jiang; Qian Xie; Wei Wang; Jinghua Wu; Qingxi Chen; Lixiang Miao (Horticulturae)
The red-flowered strawberry is a novel ornamental plant. This study aimed to assess the genetic diversity among ornamental strawberry germplasm resources. In this investigation, 17 red-flowered strawberry germplasms and 1 white-flowered strawberry germplasm were analyzed for genetic diversity and genetic relationships using a combination of phenotypic data, inter-simple sequence repeats (ISSR), and conserved DNA-derived polymorphism (CDDP) molecular markers. The results indicated that the 18 strawberry germplasms exhibited significant variability and genetic diversity at both phenotypic and molecular levels. The clustering results revealed notable differences between phenotypic clustering and molecular marker clustering, while the ISSR and CDDP markers grouped into broadly similar clusters. We further consolidated the ISSR and CDDP marker data to conduct the cluster analysis and population structure analysis of the 18 strawberry germplasms. The cluster analysis classified these germplasms into four clusters at a genetic similarity coefficient of 0.77. The population structure analysis categorized the germplasms into three groups, with 88.89% exhibiting a Q value ≥ 0.6, and 11.11% demonstrating a Q value < 0.6. This finding suggests that the genetic background of the 18 strawberry germplasms is relatively homogeneous. Notably, ‘Summer Breeze-Rose’ and ‘Summer Breeze-Cherry’ possess relatively complex genetic backgrounds (Q < 0.6). Furthermore, the floral, foliar, and plant traits of both germplasms display significant ornamental value and can serve as vital resources for the development and utilization of ornamental strawberries, as well as for the selection and breeding of new varieties.